Faktor Penghambat Pemilihan Sekolah Lanjutan Siswa Kelas IX SMP Negeri 1 Cluwak - Widiawati, Ayu Isworo; Setyowani, Ninik (Universitas Negeri Semarang, 2016)
Findings phenomena through field observations with DCM and interviews with Counselor is the existence of barriers in the selection of secondary school students of the inside and outside. The aim of research to determine the internal and external factors that inhibit the selection of secondary school students of class IX in Junior High School 1 Cluwak Pati academic year 2015/2016. This type of research is a survey research. For the population in this study were all students of class IX, namely a number of 288 students. Samples of 25% which is 72 students, and the data collection instruments constitute the psychological scale election of school. Analysis of the data used is descriptive percentage. Results found that the internal factors that inhibit the selection of secondary school students of class IX amounted to 65.35%, while external factors that inhibit the selection of secondary school students of class IX amounted to 64.58%. The conclusion is that students have the highest barriers on both factors of physical condition and the condition of a friend. Suggestions put forward can be taken into consideration in providing services related to the field of career to students.